HUBUNGAN ANTARA DUKUNGAN KELUARGA DENGAN KEMAMPUAN PERAWATAN DIRI (SELF CARE) PADA PASIEN PASCA STROKE DI RSUD PIRNGADI KOTA MEDAN - Siregar, Patimah Sari; Anggeria, Elis (Universitas Prima Indonesia, 2019)
Stroke is a condition of brain experiencing neurodegenerative disorders such as local or global, occuring in sudden emergence, progressive, and fast. Impaired nerve function in stroke caused by circulatory disorders of the brain non-traumatic. Post-stroke patients need support and help the family in the treatment himself. This study aims to determine the relationship between family support with self-care skills in patients with post-stroke. The study design is analytic survey with cross sectional approach. The study populations were 40 people and samples of this study were all post-stroke patients who were undergoing rehabilitation of physiotherapy with drawn by saturated sampling technique. The results showed that 47.5% of respondents got enough family support, and 55% of respondents have the ability of self-care with some aid. Based on the test results from Spearman Rank correlation, family support with self-care skills has a correlation coefficient of 0.38 and Sig. (2-tailed) 0.01, meaning there is a relationship between family support and self-care skills on post-stroke patients in the Royal Prima Hospital Medan. In conclusion, this study shows that family support and self-care skills strongly influence at the level of the patient's recovery. It is hoped that families to be more attentive to the needs and provide optimal support either support of awards/emotional, facilities and support information.